Doc : a novel - Russell, Mary Doria, 1950- (Random House, 2011)
After the burned body of a mixed-blood boy, Johnnie Sanders, is discovered in 1878 Dodge City, Kansas, part-time policeman Wyatt Earp enlists the help of his professional-gambler friend Doc Holliday.